Strategi Pemasaran Berbasis Inovasi Kemasan dalam Upaya Memperluas Pangsa Pasar Petis Ikan di Desa Kramat - Kusyairi Kusyairi; St Safarina; Retty Afrilia Gautami; Amelia Fatanur Baiti; Ani Nur Faizah (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Kramat Village, located in Tlanakan District, Pamekasan Regency, is a coastal area with abundant fisheries resources, one of which is fish paste (petis ikan), a long-standing local product. However, the processing businesses in this village still face challenges, particularly in terms of simple packaging and traditional marketing patterns, making it difficult to compete in modern markets. To address these issues, the Community Service Program (KKN) of Universitas Madura implemented training and mentoring focused on packaging innovation and the introduction of digital marketing strategies. The implementation methods included field observations, interviews with business actors, training to improve product quality, trial application of new packaging, and program evaluation. The results indicated significant improvements in product packaging quality, entrepreneurial skills in branding, and the utilization of social media as a promotional tool. A key achievement was the shift in entrepreneurs’ mindset from merely producing for local consumption to targeting broader markets. The program’s contribution lies in producing more competitive fish paste products, enhancing entrepreneurial literacy among the community, and strengthening the competitiveness of local MSMEs. Therefore, this KKN activity not only creates short-term impacts but also opens opportunities for sustainable community economic development.